The role of LRP1 in Aβ efflux transport across the blood-brain barrier and cognitive dysfunction in diabetes mellitus. (November 2022) - P, Xue; Zz, Long; Gg, Jiang; Lp, Wang; Cm, Bian; Yl, Wang; Chen, M.F.; W, Li
Abstract: Background: The incidence of cognitive dysfunction in diabetes is increasing yearly, which severely affects the quality of life of patients and places a heavy burden on families and society. It has been demonstrated that impaired clearance of cerebral amyloid β-protein (Aβ) is a central event in the initiation and progression of Aβ deposition and cognitive impairment in diabetic patients. However, until now, the molecular mechanism by which diabetes mellitus induces impaired clearance of Aβ has remained unclear. Objective: To investigate the role and mechanism of lipoprotein receptor-related protein 1 (LRP1) in Aβ clearance impairment and cognitive function damage caused by diabetes. Methods: SPF male C57BL/6 mice were bred, and streptozotocin (STZ) (60 mg/kg/d) was intraperitoneally injected for 5 days to establish a diabetes model. The novel object recognition test and fear conditioning test were used to assess the cognitive function of mice in each group. Western blotting, qRT-PCR, ELISAs, and immunofluorescence staining were used to detect the expression levels of Aβ and Aβ clearance-related proteins in mouse brains. HBMECs were cultured in vitro to establish the blood-brain barrier model. The clearance rate of Aβ and the expression levels of LRP1 were measured under different glucose concentration culture conditions. HBMECs were transfected with lentivirus to overexpress or knock down the LRP1, and then, the changes in Aβ clearance were detected again. We injected adeno-associated virus AAV9-SP-A-LRP1 shRNA into the tail vein of DM mice to selectively knock down LRP1 gene expression in cerebral vascular endothelial cells. Then, the cognitive function and the expression levels of Aβ and Aβ clearance-related proteins in the brains of normal, DM and LRP1 knockdown mice were detected. Results: Compared with the controls, diabetic mice showed impaired cognitive performance, increased deposition of Aβ in the brain and decreased expression of LRP1 in the brain microvasculature. In vitro experiments showed that high glucose can downregulate the expression of LRP1 in HBMECs and damage the Aβ clearance across the blood-brain barrier (BBB). The reduction in the clearance rate of Aβ induced by high glucose was reversed by LRP1 overexpression but further substantially decreased when LRP1 was knocked down. Conclusion: Hyperglycemia can impair Aβ efflux in the brain by downregulating the expression of LRP1 in the brain microvasculature, eventually resulting in cognitive impairment. Highlights: STZ-induced diabetic mice exhibit cognitive dysfunction. Diabetes induced Aβ deposition in the brain and led to cognitive dysfunction. High glucose can downregulate the expression of LRP1 in HBMECs. LRP1 crucially mediates Aβ clearance in diabetic mice.